Hiperckemia induced by strength training not influenced the rest intervals between sets - Silva, Dailson Paulucio (2012)
Creatine kinase (CK) is a marker of muscle micro damage used as biochemical monitoring in strength training (ST). Since different rest intervals between sets (IR) can interfere with the intensity and the effect of exercise, the aim of this study was to investigate the influence of two different IR (1 vs. 3 min) in the modulation of markers micro damage muscle after exercise. The study included 18 volunteers. On the first day the subjects were evaluated anthropometrically and conducted tests of one repetition maximum (1RM) for each exercise with the following sequence: bench press, pulldowns, sitting development, triceps (pulley) and biceps. After seven days off test was performed after pre collection, with a load of 85% 1RM, and were performed at random intervals of 1 to 3 minutes. Sequential blood samples were collected 24h, 48h, 72h after the test. The following week the subjects underwent the same test with IR between different series set in the previous week. Statistical analysis was conducted separately by repeated measures ANOVA for each year. No significant differences (p <0.05) significantly in serum CK between groups of different IR 24, 48 and 72 hours after the test. It was concluded that short and long IR does not differ in the number of markers generated micro damage muscle after a workout than TF.